Keunggulan dan Tantangan Sistem Pertanian Kopi dan Lada di Provinsi Lampung dalam Menghadapi Pasar Global - Ravid Ariq Arkan; Erlin Kurniati (SUAN PUBLISHER, 2025)
This study investigates the influence of labor and technology on the productivity of rubber plantations in Lampung Province through a qualitative research approach. Rubber plantations are a crucial sector for the local economy in Lampung; however, many plantations still face low productivity levels due to limitations in labor quality and insufficient technological adoption. Data were collected using in-depth interviews and field observations involving rubber farmers, plantation supervisors, and agricultural experts. The research findings highlight that skilled and experienced labor significantly contributes to better efficiency in the rubber tapping and processing stages. Moreover, the implementation of modern technology—such as advanced tapping tools, improved planting techniques, and automated equipment—can lead to higher yields and reduce production costs. Despite these potential benefits, access to modern technologies remains limited for smallholder farmers due to financial and knowledge barriers. Additionally, a lack of continuous training and support services hinders optimal workforce performance. To address these challenges, this study suggests increasing government and private sector support for training programs and facilitating access to affordable, appropriate technologies. Strengthening these two key factors—labor competency and technological innovation—will enhance the productivity, sustainability, and competitiveness of rubber plantations in Lampung Province, contributing to broader regional economic development